Genetic control of the operculum and capsule morphology of Eucalyptus globulus - Hernandez, Mariano Agustín; Butler, Jakob B.; Ammitzboll, Hans; Weller, James L.; Vaillancourt, René E.; Potts, Brad M. (Oxford University Press, 2022)
The petaline operculum that covers the inner whorls until anthesis and the woody capsule that develops after fertilization are reproductive structures of eucalypts that protect the flower and seeds. Although they are distinct organs, they both develop from flower buds and this common ontogeny suggests shared genetic control. In Eucalyptus globulus their morphology is variable and we aimed to identify the quantitative trait loci (QTL) underlying this variation and determine whether there is common genetic control of these ecologically and taxonomically important reproductive structures.